Hungary : Selected Issues. (IMF Staff Country Reports; Country Report, 2019)
This Selected Issues paper describes and discusses potential implications of recent changes in Hungary's public debt strategy. Special attention is paid to the motivation for, and recent experiences with, the 'Hungarian Government Security Plus Scheme' (MAP+) for physical persons, introduced in June 2019. One of the main benefits of retail bonds is that they usually are perceived as more stable funding. However, it is argued that MAP+ should be continuously monitored to ensure its objectives are achieved in the most cost-efficient manner and to avoid unintended distortions. The paper also focuses on specific public debt management policies in Hungary and it briefly discusses experiences with the retail bond programs in other countries but focuses mainly on the MAP+ bond, the initial experience with this bond, and elaborates on its potential implications. MAP+ has many reasonable objectives, although some of them, such as higher a savings rate of households and reduced external indebtedness, are to a major extent driven by macroeconomic policies. Going forward, the question remains whether these objectives can be achieved by appreciably lower cost to the budget given less expensive alternative funding sources and policy options. Public debt management also needs to respond to changing market conditions.